Representation Dilemmas in Civil Society Organisations in Global Health Donor Resource Prioritisation Decisions: the case of PEPFAR in South Africa - Banda, Amanda Chawo (My University, 2019)
Juxtaposing citizen and civil society representation in a democracy, some scholars assert that civil society organisations assume representation in their public interest advocacy work on behalf of marginalized populations. They argue that civil society organisations lack formal members or constituents to authorise and hold them accountable as representatives. I conducted a study to understand the representation dilemmas in civil society organisations in global health donor resources prioritisation decisions looking at the case of United States President’s Emergency Plan for AIDS Relief (PEPFAR) in South Africa between 2016 and 2018. Specifically, I assessed, what and who gives civil society authority to speak on the citizens’ behalf, how they are held accountable by the people they represent and how internally democratic civil society organisations are. A mixed method of questionnaire and in-depth interviews was used. In some cases, I observed some meetings and engagement processes between PEPFAR and civil society organisations. Using a purposive sampling method, a total of ten participants were interviewed. One was working for PEPFAR and nine participants were staff who ‘represent’ people living with HIV in their participation in the PEPFAR’s resource prioritisation processes. Thematic content analysis was used to analyse and interpret the interviews. Democratic theory, particularly examining the concept of representation, was the theoretical framework used to guide the discourse and interpretation of the research study. The study suggests that there was both authorised, delegated as well as assumed representation in the PEPFAR resource prioritisation. There is either formal independent electoral systems in place to elect and appoint representatives or membership based structures. The study found deep polarisation of civil society organisations. On one camp is a group with formal electoral systems group engaging in an ‘invited’ space through the SANAC Civil Society Forum. On the other is a camp with membership based structures participating in an ‘invented’ space. I argue while there are deep internal democratic flaws and gaps, there was no evidence of the impact of this polarisation on the legitimacy of the representation work done by both camps. In both camps, accountability and responsiveness mechanisms exist but are very weak. The study found participation remains very elite with those in Director role engaging with PEPFAR every week. Two out of the eight representatives were in contact at least once every two to three months, another two were in contact once every six months with the remaining four in contact once every twelve months only for the consultation processes. I argue that representatives’ participation in the process is only for compliance of the requirements of the process. There was no little evidence of issues raised by the representatives translate into changes to the initial proposed prioritisation of resources, design of programmes, and monitoring of implementation.
A research report submitted in partial fulfilment of the requirements for the degree of Masters in Political Studies
Keywords: Civil society; Non-governmental organizations; International cooperation